2006
DOI: 10.1128/aac.50.4.1538-1540.2006
|View full text |Cite
|
Sign up to set email alerts
|

Gatifloxacin Resistance and Mutations in gyrA after Unsuccessful Helicobacter pylori Eradication in Japan

Abstract: A high resistance rate (47.9%) to gatifloxacin (GAT; 8-methoxy fluoroquinolone) in Helicobacter pylori (H. pylori) strains from 48 Japanese patients is observed after unsuccessful H. pylori eradication. A significant association between MICs for GAT equal to or above 1 g/ml and mutations of the gyrA gene of H. pylori was demonstrated.Resistance to antibiotics is the major cause of the failure to eradicate Helicobacter pylori. For such cases, alternative regimens need to be developed.Perri et al. have reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
71
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 13 publications
4
71
1
1
Order By: Relevance
“…All patients underwent upper-gastrointestinal endoscopy; biopsy specimens obtained from the greater curvature of the upper corpus were then used to isolate H. pylori. The clinical isolates of H. pylori used in the present study were previously examined and reported only in terms of gyrA mutation and the MIC for GAT (17). In addition to 48 previous isolates (17), isolates with known GAT MICs were examined for gyrA mutation (KS0203, KS0205, KS0193, and KS0195).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All patients underwent upper-gastrointestinal endoscopy; biopsy specimens obtained from the greater curvature of the upper corpus were then used to isolate H. pylori. The clinical isolates of H. pylori used in the present study were previously examined and reported only in terms of gyrA mutation and the MIC for GAT (17). In addition to 48 previous isolates (17), isolates with known GAT MICs were examined for gyrA mutation (KS0203, KS0205, KS0193, and KS0195).…”
Section: Methodsmentioning
confidence: 99%
“…The MIC was defined as the lowest concentration of antibiotic that completely inhibited the growth of the inoculum. Isolates were considered resistant to GAT if the MIC of the drug was Ն1 g/ml (2,11,14,17).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCR was performed with 35 cycles of denaturation at 94 C for 30 seconds (s), annealing at 52 C for 30 s, and extension at 72 C for one minute. 4,5,8,12 PCR products for sequencing were purified with a QIAquick Gel Extraction Kit (QIAGEN). PCR templates of all strains were sequenced directly on both strands by the BigDye Terminator Cycle Sequencing method using the Applied Biosystems 3100 Genetic Analyzer (Applied Biosystems).…”
Section: Study Design and Study Populationmentioning
confidence: 99%